2022
DOI: 10.1186/s12885-022-09957-8
|View full text |Cite
|
Sign up to set email alerts
|

Composite scoring system and optimal tumor budding cut-off number for estimating lymph node metastasis in submucosal colorectal cancer

Abstract: Background Tumor budding is associated with lymph node (LN) metastasis in submucosal colorectal cancer (CRC). However, the rate of LN metastasis associated with the number of tumor buds is unknown. Here, we determined the optimal tumor budding cut-off number and developed a composite scoring system (CSS) for estimating LN metastasis of submucosal CRC. Methods In total, 395 patients with histologically confirmed T1N0–2M0 CRC were evaluated. The clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…We identified 3451 records from various databases until December 10, 2022. After screening for duplicates, we included 64 studies with 18,097 patients, 17,18,22,36–96 of them, 59 studies evaluated the diagnostic accuracies of HE and additional staining for LVI in LNM in patients with T1 CRC, four reported the interobserver agreement among pathologists for positive LVI, and one reported both outcomes, with eight studies comprising 4062 patients in multivariable analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 3451 records from various databases until December 10, 2022. After screening for duplicates, we included 64 studies with 18,097 patients, 17,18,22,36–96 of them, 59 studies evaluated the diagnostic accuracies of HE and additional staining for LVI in LNM in patients with T1 CRC, four reported the interobserver agreement among pathologists for positive LVI, and one reported both outcomes, with eight studies comprising 4062 patients in multivariable analysis.…”
Section: Resultsmentioning
confidence: 99%
“…TB is a highly invasive tumour subpopulation that can evade the immune response 27 , 28 . As an emerging prognostic biomarker in CRC 11 , 29 , 30 , it has been strongly correlated with higher tumour grade, the presence of lymph node metastases and perineural invasion 12 , 13 . The prognostic value of TB has been validated in five independent studies, involving a total of 1978 patients with stage II CRC 14–18 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumour budding (TB) was first described by Imai in the 1950s 10 and is defined as the presence of single cancer cells or clusters of up to four cells at the invasive tumour front 11 . It has been found to be strongly correlated with higher tumour grade, the presence of lymph node metastases, perineural invasion and immune escape 12 , 13 . Five independent studies demonstrated that patients with low-grade tumour budding (Bd1) had a 5-year disease-specific survival (DSS) of 89–98 per cent, while patients with intermediate-grade (Bd2) or high-grade tumour budding (Bd3) have a significantly worse 5-year DSS of 52–80 per cent 14–18 .…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is among the commonest cancers diagnosed in females. 1 Breast cancer is the main cause of death and is the most diagnosed cancer, exceeding lung cancer. Breast cancer is ranked first among Indian females, 2 and men contributes 0.5 to 1% of breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 7.8 million women who diagnosed with breast cancer in the past 5 years were alive at the end of 2020. 1,3 Breast cancer is a risk in both rural and urban India and it accounts for 14% cancers in India. A breast cancer case in Indian women is diagnosed every four minutes.…”
Section: Introductionmentioning
confidence: 99%